2022
DOI: 10.3389/fimmu.2022.865845
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Immunological and Clinical Predictors of COVID-19 Severity and Sequelae by Mathematical Modeling

Abstract: Since its emergence as a pandemic in March 2020, coronavirus disease (COVID-19) outcome has been explored via several predictive models, using specific clinical or biochemical parameters. In the current study, we developed an integrative non-linear predictive model of COVID-19 outcome, using clinical, biochemical, immunological, and radiological data of patients with different disease severities. Initially, the immunological signature of the disease was investigated through transcriptomics analysis of nasophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Furthermore, the results from real life COVID-19 data also support the conclusion that the proposed LogF outperforms both the Firth and Ibrahim methods. These results from the application agree with the clinician's theory that admission to ICU for the COVID-19 patient is significantly explained by the three factors that is, conjuctivitis, unconsciousness and having a neurological condition [36,37]. We also note that using the complete case analysis alone in modeling may lead to incorrect logit model, as it may be determined that a predictor is not significant, when actually the reverse is true or otherwise.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the results from real life COVID-19 data also support the conclusion that the proposed LogF outperforms both the Firth and Ibrahim methods. These results from the application agree with the clinician's theory that admission to ICU for the COVID-19 patient is significantly explained by the three factors that is, conjuctivitis, unconsciousness and having a neurological condition [36,37]. We also note that using the complete case analysis alone in modeling may lead to incorrect logit model, as it may be determined that a predictor is not significant, when actually the reverse is true or otherwise.…”
Section: Discussionsupporting
confidence: 79%
“…Twenty-two studies ( 5 , 18 , 19 , 23 , 26 33 , 35 , 37 , 38 , 40 , 47 , 48 , 51 , 52 , 55 , 56 ) (16,574 subjects) reported the mean level of serum albumin ALB. The mean level of albumin was lower in the severe COVID-19 group than in the non-severe group (WMD = −4.52 g/L, 95% CI: −6.28 to −2.75), with high heterogeneity ( I 2 = 99.9%, P Heterogenity = 0.000) ( Figure 3E , Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies ( 1 , 5 , 18 , 19 , 26 , 29 , 32 , 37 , 42 , 48 , 51 54 ) (9,739 subjects) reported the mean level of PT. The mean level of PT was significantly higher in severe cases (WMD = 0.84 s, 95% CI: 0.46–1.23), with high heterogeneity ( I 2 = 99.4%, P Heterogenity = 0.000) ( Figure 3F , Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The severe and critical COVID-19 patients included in this study had increased levels of IL-6, IL-10, sFas, granulysin and IP-10, and non-surviving patients had increased levels of IL-6, IL-8, IL-10, IFN-β, sFas and IP-10. IL-6 has been identified as a biomarker for disease progression and fatality in COVID-19 ( Santa Cruz, et al, 2021 ), while IL-8, IL-10 and IP-10 have been evaluated as predictors of disease severity ( Elemam et al, 2022 , Guo et al, 2021 ). IP-10 (CXCL10) limits endothelial repair ( Lupieri, et al, 2020 ), which may promote thrombosis in critical and severe COVID-19 patients ( Chen, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%